(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Japan implemented new legislation to prevent the abuse of persons with disabilities on Oct 1, 2012. Many specialists from various domains participated in the development of interventions to prevent such abuse. Here, we conducted a pilot analysis to examine the cost of such interventions and to explore differences in resources. In particular, we compared resources for the assistance of victims with intellectual disabilities with those for the assistance of victims with other disabilities. We requested the enrollment of the anonymous case records of 16 local governments. Thirteen municipal/certified centres reported 41 cases, including 42 victims. Of them, 27 victims had intellectual disabilities. We calculated both the time and human/social resources consumed per case until the resolution of the case. Although the median length of time from the start of the intervention until the solution of the claimed crisis seemed longer in cases abused by their families, an analysis of 22 familial cases did not reveal a significant relationship between the type of disability and the resource. Although the existence of intellectual disabilities did not seem to impact the resource, our method of analysis worked well. The accumulation of more cases is warranted.